OBRERISMO AND ANTIGUERRERISMO, WAYS OF CONNECTION BETWEEN INTELLECTUALS, ARTISTS AND COMMUNIST PARTIES IN THE SOUTH CONE, 1930 DECADE - Prado Acosta, Laura (Revista de Historia Social y de las Mentalidades, 2024)
The studies about the relationship between intellectuals, artists and communist parties usually focus in the antifascist times, shaped by the VII Congress of the Comintern. This article inquires in previous connections, generated by a pro-worker sensibility, and by the reject to the Guerra del Chaco (1932-1935). The change in the period is done analyzing three stages, in Uruguay, Argentina y Chile, it’s shown the multiple projects, tensions and strategies followed by the communists intelectualls and artists.